Institutional trust and entrepreneurs' export behavior: An international analysis - De Anda, Felipe (2023)
The main goal of this research is to test the association between trust in institutions—e.g., police, law courts, property rights, government regulations, and public and private organizations—and entrepreneurial internationalization. The longitudinal analysis uses data obtained from the Global Entrepreneurship Monitor (GEM), the Heritage Foundation Index of Economic Freedom (IEF), World Bank Worldwide Governance Indicators (WGI), and World Development Indicators (WDI) for a sample of 88 countries during 2013-2018. Using factor analysis and panel data techniques that control for potential endogeneity, institutional trust is found to be significantly correlated with internationalization; however, this result is only valid for small and medium-sized enterprises (SMEs) in developing countries. Therefore, entrepreneurs from developing economies have to overcome the lack of institutional trust to successfully carry out their internationalization process.